Waste to wealth: Microbial-based sustainable valorization of cotton biomass, processing waste and by-products for bioenergy and other value-added products to promote circular economy - Ajinath Dukare; Rahul Yadav; Sheshrao Kautkar; Pandiyan Kuppusamy; Kanika Sharma; Anam Shaikh; Anagha Pawar; Amruta Gadade; Nadanathangam Vigneshwaran; Sujata Saxena; Sujeet Kumar Shukla (Waste Management Bulletin)
Cotton-based textile industries sustain millions of people’s livelihoods and are significant sources of revenue for the nation’s economy. The enormous amount of biomass, processing wastes, and byproducts generated during cotton processing are usually landfilled or incinerated, which is the cause of environmental pollution and health hazards. Cotton biomass, mainly comprised of cellulose, hemicellulose, and lignin, represents a sustainable feedstock for the fermentative production of value-added bioproducts using microorganisms. Advances in microbial biotechnology have led to the effective valorization of cotton biomass and processing waste into valuable products. To date, cotton-based waste biomaterial has been utilized for microbial production of biofuel, hydrogen, biomethane, enzymes, organic acids, bio-enriched compost, and as a substrate for mushroom cultivation. Furthermore, the use of cotton biomass for developing fungal mycelial-based composite and eco-friendly packaging material is documented. Cotton seed meal, an essential byproduct of the cottonseed industry, is converted into more proteinous products and bioactive peptides via microbial-mediated degossypolization and fermentation. The potential of modern metabolic engineering tools such as gene sequencing and assembly, genome editing, clustered regularly interspaced short palindromic repeats (CRISPR), and cell surface engineering for microbial strain development is summarized. This is the first comprehensive review highlighting the aspects of cotton biomasses and byproducts, their structural composition, pretreatment strategies, and microbial approaches for bioconversion into valuable compounds. This document presents the cotton processing industry with an innovative pathway towards a waste-to-wealth solution via microbial-based biorefineries.